Efektivitas Media Pembelajaran Video Animasi dalam Meningkatkan Motivasi Belajar PAI Siswa - Iqbal, Muhammad; Nuraini, Ryan (Kartika: Jurnal Studi Keislaman, 2026)
This research stems from academic anxiety regarding the low learning motivation of students in Islamic Education (PAI), which is still dominated by conventional lecturing methods, making abstract materials difficult to internalize for the digital generation. This study aims to analyze the implementation of animated video media and its influence on the transformation of student learning motivation at SMPI Sunan Bonang, Jember. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The research findings indicate a trend towards increased attention, relevance and confidence among students in understanding complex Islamic Education (PAI) material, such as the stories of the prophets and the history of Islam. This media acts as an instrument for reconstructing spiritual imagination, bridging theoretical concepts into concrete visual experiences. The implications of this research emphasize that the effectiveness of PAI learning in the digital era highly depends on teachers' mastery of the Technological Pedagogical Content Knowledge (TPACK) framework. This study recommends the development of a PAI curriculum that integrates visual literacy as a strategy for the holistic internalization of Islamic values